2017
DOI: 10.1002/ejhf.1054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systolic blood pressure on the safety and tolerability of initiating and up‐titrating sacubitril/valsartan in patients with heart failure and reduced ejection fraction: insights from the TITRATION study

Abstract: The majority of patients (>80%) with SBP of ≥100 mmHg achieved and maintained the target dose of sacubitril/valsartan if the treatment was titrated gradually. These findings suggest that low SBP should not prevent clinicians from considering the initiation of sacubitril/valsartan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 30 publications
2
50
0
5
Order By: Relevance
“…In a post-hoc analysis of TITRATION, > 80% of patients with SBP ≥ 100 mmHg achieved and maintained the target dose of sacubitril/valsartan if the treatment was titrated gradually. 22 We observed that ACEI/ARB-naïve patients were similar to patients on an ACEI or ARB able to initiate, up-titrate and maintain sacubitril/valsartan. These findings address a key question that had remained unanswered in the PARADIGM-HF study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a post-hoc analysis of TITRATION, > 80% of patients with SBP ≥ 100 mmHg achieved and maintained the target dose of sacubitril/valsartan if the treatment was titrated gradually. 22 We observed that ACEI/ARB-naïve patients were similar to patients on an ACEI or ARB able to initiate, up-titrate and maintain sacubitril/valsartan. These findings address a key question that had remained unanswered in the PARADIGM-HF study.…”
Section: Discussionmentioning
confidence: 74%
“…Similar to ACEI or ARB management, slow up‐titration to target dose in the highly vulnerable post‐ADHF phase is recommended. In a post‐hoc analysis of TITRATION, > 80% of patients with SBP ≥ 100 mmHg achieved and maintained the target dose of sacubitril/valsartan if the treatment was titrated gradually . We observed that ACEI/ARB‐naïve patients were similar to patients on an ACEI or ARB able to initiate, up‐titrate and maintain sacubitril/valsartan.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, there was a greater risk of symptomatic hypotension in the LCZ696 arm than in the enalapril arm . Although LCZ696 dose titration to the target dose seemed to be feasible in the majority (> 80%) of patients with systolic blood pressure > 100 mmHg enrolled in another randomized study, more than 90% of the study participants had tolerated an ACEi/ARB prior to screening, whereas an open‐label 5‐day run‐in phase of LCZ696 50 mg twice daily was also included. Another randomized trial assessing the feasibility and safety of pre‐discharge vs. post‐discharge initiation of LCZ696 in HFrEF patients hospitalized for HF decompensation was recently presented .…”
Section: Discussionmentioning
confidence: 99%
“…Unmet needs regard implementation of this drug. Hypotension, above all if symptomatic, remains a major limitation, and a strategy of slow dose titration may allow better tolerability and adherence to treatment . In‐hospital initiation may also allow treatment implementation.…”
Section: Treatmentmentioning
confidence: 99%
“…Hypotension, above all if symptomatic, remains a major limitation, and a strategy of slow dose titration may allow better tolerability and adherence to treatment. 16 In-hospital initiation may also allow treatment implementation. Sacubitril/valsartan initiation in an in-hospital setting vs. an outpatient setting, such as in PARADIGM-HF, was compared in the Comparison of Pre-and Post-discharge Initiation of LCZ696 Therapy in HFrEF Patients After an Acute Decompensation Event (TRANSITION) study.…”
Section: Introductionmentioning
confidence: 99%